The Influence of Specific Learning Disabilities on the Work of an English Language Teacher - Koditková, Kateřina (Univerzita Pardubice, 2024)
This diploma thesis investigates the influence of specific learning disabilities, especially dyslexia, dysgraphia, and dysorthography, on the professional practice of English language teachers. Through a qualitative method of research, seven English language teachers with specific learning disabilities participated in semi-structured interviews to explore their experiences and compensatory strategies. Findings reveal challenges in writing and memory retention, countered by detailed lesson planning, visualisation aids, and technology. Despite difficulties, teachers exhibit confidence in maintaining teaching standards and positively impacting students' English proficiency. The research advocates for the support and acceptance of teachers with specific learning disabilities within educational settings, emphasising the need for destigmatization and increased awareness.
Vliv Specifických Poruch Učení na Práci Učitele Anglického jazyka
Keywords: specifické poruchy učení; dyslexie; dysgrafie; dysortografie; učitelé anglického jazyka; učitelé angličtiny se specifickými poruchami učení; kompenzační strategie; specific learning disabilities; dyslexia; dysgraphia; dysortography; English language teacher; English teachers with specific learning disabilities; compensatory strategies